The mediating role of trust on the influence of perceived easement and perceived security towards digital payment customer loyalty BSI mobile in the community of Medan City - Hanapi Umar Hasibuan; Efry Kurnia (Jurnal Mantik, 2024)
Research purposes This is to know and analyze the influence of perception ease and perception security on loyalty customers mediated trust in a way direct nor in a way No direct. The approach used in the study is the causal approach. The population in study This is all over Medan city residents who use BSI Mobile. Deep sample study This uses the formula Lemeshow totaling 96 people. Deep data collection techniques study This uses technique questionnaire. Deep data analysis techniques study This approach quantitative uses analysis statistics using Auter Model Analysis, Inner Model Analysis, and Hypothesis Testing. Deep data processing study This uses the PLS (Partial Least Square) software program. Research result This proves that in a way direct perception ease, perception security and trust influential significant to loyalty, perception ease and perception security influential significant to trust and so No direct trust mediate influence perception ease and perception security to loyalty